2019
DOI: 10.1073/pnas.1903259116
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the activation energy barrier for the nucleation of single nanosized vapor bubbles

Abstract: Heterogeneous bubble nucleation is one of the most fundamental interfacial processes that has received broad interest from diverse fields of physics and chemistry. While most studies focused on large microbubbles, here we employed a surface plasmon resonance microscopy to measure the nucleation rate constant and activation energy barrier of single nanosized embryo vapor bubbles upon heating a flat gold film with a focused laser beam. Image analysis allowed for simultaneously determining the local temperature a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 42 publications
0
58
0
Order By: Relevance
“…If the earliest label-free imaging of HER at Pt NPs by SPRM suggested I opt changes were due to local molecular H + or dissolved H 2 concentration gradient around catalytic NPs, 41 we believe such change results from H 2 gas NB formation, as demonstrated later by White et al, who showed that single gas NBs can nucleate and grow from electrochemical reactions at nanoelectrodes. 6 The optical visualization of NBs on surfaces was further confirmed (i) from fluorescence imaging (rigorously of the NBsolution interface) during HER at electrode surface or NPs, or (ii) from label-free imaging of gas NBs, either by SPRM at heated surfaces 27,42 or dark field microscopy for qualitative benchmarking of NPs electrocatalytic activity. 3,43 We explore here the possibility of analyzing quantitatively the NBs formation from the variations of the local optical intensity, I opt , recorded by IRM.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…If the earliest label-free imaging of HER at Pt NPs by SPRM suggested I opt changes were due to local molecular H + or dissolved H 2 concentration gradient around catalytic NPs, 41 we believe such change results from H 2 gas NB formation, as demonstrated later by White et al, who showed that single gas NBs can nucleate and grow from electrochemical reactions at nanoelectrodes. 6 The optical visualization of NBs on surfaces was further confirmed (i) from fluorescence imaging (rigorously of the NBsolution interface) during HER at electrode surface or NPs, or (ii) from label-free imaging of gas NBs, either by SPRM at heated surfaces 27,42 or dark field microscopy for qualitative benchmarking of NPs electrocatalytic activity. 3,43 We explore here the possibility of analyzing quantitatively the NBs formation from the variations of the local optical intensity, I opt , recorded by IRM.…”
Section: Resultsmentioning
confidence: 89%
“…the wetting of the NP). 27 Surface chemistry could play similarly a significant role in the overall electrochemical activity of the NP. The capping agent of the NP is expected to control both the electrical contact between the NP and the electrode and the electron transfer rate for HER at the NP-solution interface.…”
Section: Resultsmentioning
confidence: 99%
“…Single nanoparticles induce the localized enhancement of SPPs, and transforms to far field via leakage radiation for fast and label-free detection [5,6]. This method has been widely applied to chemistry and biology, such as bidirectional electron transfers visualizing [7], local activation energy barrier measuring [8], thermal hysteresis imaging of single spin-crossover nanoparticles [9], and single liposomes and virus detection [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Plasmonic-enhanced spectroscopy 18,19 exploits the excellent optical performance of advanced plasmonic nanostructures and possesses noninvasive feature with superior sensitivity and compatibility in monitoring a variety of chemical processes, including heterogeneous catalysis [20][21][22] , electrochemistry [23][24][25] and phase transition [26][27][28] . Thereby, plasmonic-enhanced spectroscopy may possess the ability to differentiate oxygen compositions during OER at EEIs.…”
Section: Introductionmentioning
confidence: 99%